ALK-rearranged Renal Cell Carcinoma (RCC): A Report of 2 Cases and Review of the Literature Emphasizing the Distinction Between VCL-ALK and Non-VCL-ALK RCC. (October 2021) - Wangsiricharoen, Sintawat; Zhong, Minghao; Ranganathan, Sarangarajan; Matoso, Andres; Argani, Pedram
Anaplastic lymphoma kinase (ALK) rearrangement-associated renal cell carcinoma ( ALK -rearranged RCC) is a new provisional entity that has been included in the 2016 World Health Organization classification of RCCs. We report 2 cases of ALK -rearranged RCC, 1 with a vinculin-ALK ( VCL-ALK ) fusion and the other with an EML4-ALK fusion. The VCL-ALK RCC occurred in a 14-year-old girl with sickle cell trait and showed features similar to previously described VCL-ALK RCCs, including medullary epicenter, solid architecture, and polygonal cells with cytoplasmic vacuoles. The EML4-ALK RCC occurred in a 14-year-old boy with no evidence of sickle cell trait and had multiple less-specific growth patterns comprising tubular, solid, and tubulopapillary architectures in the desmoplastic stroma, reminiscent of collecting duct carcinoma. Both tumors demonstrated cytoplasmic and membranous ALK protein expression by immunohistochemistry. Fluorescence in situ hybridization confirmed the ALK gene rearrangements in both cases. On review in the literature, we found that solid architecture and cytoplasmic vacuoles were present significantly more frequently in VCL-ALK RCC than in non- VCL-ALK RCC, supporting the distinctive nature of the former.